PENGARUH KESEHATAN FISIK, PSIKOLOGIS, HUBUNGAN SOSIAL DAN LINGKUNGAN TERHADAP KUALITAS HIDUP LANSIA PADA PANDEMI COVID-19 DI PUSKESMAS CIPUTAT TANGERANG SELATAN TAHUN 2022 - Ruth Nikita Krishnamurti Simanjuntak, (2022)
The COVID-19 pandemic has an impact on aspects of the elderly's life, in addition to having an impact on the physical and psychological health of the elderly, restrictions on social activities during the pandemic can affect social relationships and the environment around the elderly which can affect the quality of life. This study aims to examine the influence of physical, psychological and social health on the quality of life of the elderly during the COVID-19 pandemic. This type of research is an analytic observational with a cross-sectional design, using WHOQOL-BREF as the research instrument. The elderly population at the Ciputat Public Health Center, South Tangerang, was selected using a simple random sampling method of 96 respondents. The results of the univariate analysis using the frequency distribution showed a dominant picture in terms of physical, psychological, social relationships, environment and quality of life. The results of the bivariate analysis using the alternative Fisher's Exact Test showed a significant effect on physical health (p-value = 0.009), psychological (p-value = 0.013), social relations (p-value = 0.000) and the environment (p-value = 0.000 ) on quality of life. The results of multivariate analysis using logistic regression showed that the environment was the most dominant variable on the quality of life of the elderly at the Ciputat Public Health Center, South Tangerang 2022 (Odds Ratio = 418.2; CL95% = 7.80 - 22405.6; p < 0.003; Coefficient B = 6.036 ).